2011
DOI: 10.1590/s1413-81232011001000020
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde exposure and asthma in children: a systematic review

Abstract: Formaldehyde exposure and asthma in children: a systematic review Exposição ao formol e asma em crianças: uma revisão sistemáticaResumo Apesar de múltiplos estudos publicados sobre a associação entre exposição ao formol e asma infantil, uma relação consistente ainda não foi identificada. Nós relacionamos os resultados de revisão de estudos publicados a fim de fornecer uma imagem mais compreensível desta relação. Após pesquisa, foram identificados sete estudos que proviam resultados quantitativos sobre a associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 24 publications
1
75
0
1
Order By: Relevance
“…They also promote sensitization mechanisms by means of a synergist effect, thus causing an allergic reaction with a smaller quantity of allergen, as well as the reduction in s-nitrosoglutathione, which is an endogenous bronchodilator. 41,42 Radon decays into solid radioactive elements, like polonium, which release alpha particles, a form of high-energy radiation that can deteriorate human DNA. The energy of these particles is regardless of radon concentrations, so that even at low concentrations it can be harmful, and therefore the toxicity of radon does not require a threshold level.…”
Section: Physiopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…They also promote sensitization mechanisms by means of a synergist effect, thus causing an allergic reaction with a smaller quantity of allergen, as well as the reduction in s-nitrosoglutathione, which is an endogenous bronchodilator. 41,42 Radon decays into solid radioactive elements, like polonium, which release alpha particles, a form of high-energy radiation that can deteriorate human DNA. The energy of these particles is regardless of radon concentrations, so that even at low concentrations it can be harmful, and therefore the toxicity of radon does not require a threshold level.…”
Section: Physiopathologymentioning
confidence: 99%
“…A recent systematic review seems to confirm an increase in the prevalence of asthma in children of 3% for every 10 g/m 3 of increase in formaldehyde levels. 42 A case-control study with children demonstrated that the exposure to other VOC like acetaldehyde or toluene significantly increases the prevalence of asthma. The effect seems different depending on whether the residence is urban or rural or on the season of the year.…”
Section: Lung Cancermentioning
confidence: 99%
“…These ACA compounds and other groups of low-molecular-weight disinfection by-products (DBPs, <300 Da) formed upon the oxidation of natural organic matter (NOM) or effluent organic matter (EfOM) that is present in drinking water and wastewater, respectively may be significant for several reasons. Some aldehydes (e.g., formaldehyde, acetaldehyde, glyoxal and methylglyoxal) are toxic and had been classified as known carcinogens or suspected carcinogens (Richardson et al, 2007;McGwin et al, 2009). They may also be responsible for the undesirable odor in the treated waters because of their very low odor detection thresholds, e.g., 4.0 lg L À1 for acetaldehyde (Dą browska and Nawrocki, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Acute and chronic inhalation exposures to formaldehyde in humans, particularly children, can result in respiratory symptoms and irritations of the eyes, nose, and throat (McGwin, Jr. et al, 2010). The U. S.…”
Section: Introductionmentioning
confidence: 99%